Психічні стани людини як предмет емпіричного дослідження у психології - Ларіонов, С. О.; Larionov, S. O.; Макаренко, П. В.; Makarenko, P. V. (Вісник Національного університету оборони України. - 2014. - Вип. 1(38). - С. 230-234, 2014)
Стаття присвячена теоретичному аналізу психологічної категорії «психічний стан». Визначені основні напрямки вивчення психічних станів людини у психологічній науці. Узагальнені підходи до визначення сутності, структури та функцій психічних станів людини. Проаналізовані дослідницькі парадигми та основні шляхи емпіричного вивчення психічних станів людини.

The article is devoted to the theoretical analysis of psychological category "mental state". There are identified the basic directions of the exploring of human mental states in psychological science. In the article summarizes the approaches to the definition of the structure and function of human mental states. There is showed the relation between mental processes, states and personality traits. Attention is accented to the role of experiencing in the process of differential diagnosis of mental states. There is analyzed the typical errors of selfesteem person's mental state and the adequacy of psychodiagnostic methods of its study. There are analyzed research paradigms and basic ways of empirical study of human mental states.

Статья посвящена теоретическому анализу психологической категории «психическое состояние». Определены основные направления изучения психических состояний человека в психологической науке. Обобщены подходы к определению сущности, структуры и функций психических состояний человека. Проанализированы исследовательские парадигмы и основные пути эмпирического изучения психических состояний человека.
Mental state of human as a subject of empirical research in psychology
Keywords: психічний стан; mental state; психическое состояние; особистість; personality; личность; емпіричне дослідження; empirical research; эмпирическое исследование; психологічна наука; psychological science; психологическая наука